2018
DOI: 10.3389/fphys.2018.00105
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Renal Fibrosis: Recent Insights for the Development of Novel Therapeutic Strategies

Abstract: Chronic kidney disease (CKD) is a significant worldwide healthcare problem. Regardless of the initial injury, renal fibrosis is the common final pathway leading to end stage renal disease. Although the underlying mechanisms are not fully defined, evidence indicates that besides inflammation, oxidative stress plays a crucial role in the etiology of renal fibrosis. Oxidative stress results from an imbalance between the production of free radicals that are often increased by inflammation and mitochondrial dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 111 publications
2
71
0
3
Order By: Relevance
“…DN is a serious and common complication of diabetes, which leads to end‐stage kidney disease, and therefore, it is important to illuminate the mechanisms and explore the effective therapeutic strategy for DN. Specific treatment of patients with diabetic nephropathy can be divided into 4 major arenas: cardiovascular risk reduction, glycemic control, blood pressure control, and inhibition of the renin‐angiotensin system (RAS) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…DN is a serious and common complication of diabetes, which leads to end‐stage kidney disease, and therefore, it is important to illuminate the mechanisms and explore the effective therapeutic strategy for DN. Specific treatment of patients with diabetic nephropathy can be divided into 4 major arenas: cardiovascular risk reduction, glycemic control, blood pressure control, and inhibition of the renin‐angiotensin system (RAS) .…”
Section: Discussionmentioning
confidence: 99%
“…Our current study had demonstrated that FGF1 treatment blocked diabetes‐associated α‐SMA overexpression and collagen accumulation. Histologically, progressive kidney disease is marked by renal fibrosis and glomerulosclerosis . It is well known that α‐SMA is the marker of cell transdifferentiation, including epithelial–mesenchymal transition (EMT) and fibroblast activation into myofibroblast, which importantly contributes to the progression of CKD .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations